2021
DOI: 10.1007/s00259-021-05371-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and gene expression profile to characterise the disease and predict outcome in patients with lung cancer

Abstract: Objective The objectives of our study were to assess the association of radiomic and genomic data with histology and patient outcome in non-small cell lung cancer (NSCLC). Methods In this retrospective single-centre observational study, we selected 151 surgically treated patients with adenocarcinoma or squamous cell carcinoma who performed baseline [18F] FDG PET/CT. A subgroup of patients with cancer tissue samples at the Institutional Biobank (n = 74/151)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 56 publications
0
42
0
1
Order By: Relevance
“…Other literatures reported that the combination of multiple radiomic features, which is often defined as the radiomic signature (RS), may hold higher prognostic value than the single feature [16,17]. In addition, RS combined with clinical or genomic data can produce robust and improved medical decision-making [18,19]. However, to the best of our knowledge, the RS based on [ 18 F]FDG PET/CT for prognosis assessment of DLBCL has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Other literatures reported that the combination of multiple radiomic features, which is often defined as the radiomic signature (RS), may hold higher prognostic value than the single feature [16,17]. In addition, RS combined with clinical or genomic data can produce robust and improved medical decision-making [18,19]. However, to the best of our knowledge, the RS based on [ 18 F]FDG PET/CT for prognosis assessment of DLBCL has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…There were eight studies addressing lung, head, and neck cancer (see complete data in Table S2 in Supplementary Materials ). All of the studies used CT-derived radiomic features and two studies [ 32 , 34 ] also had PET FDG-derived radiomic features. Though there was a high proportion with a decent number of included patients (24–837, mean 310), most studies had few patients with genetic data and only one study had data on multiple genes for more than 100 patients [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The handling of genetic data in the studies on lung cancer can be divided into three subgroups. Two studies [ 28 , 32 ] focused solely on the EGFR mutation , three studies [ 31 , 33 , 34 ] looked for correlations with multiple single genes and three studies [ 28 , 29 , 51 ] focused on correlation to gene pathway alteration.…”
Section: Resultsmentioning
confidence: 99%
“…MXD3 has been shown to predict poor prognosis in clear cell renal cell carcinoma ( Zhang et al, 2021 ) and hepatocellular carcinoma ( Xu et al, 2019 ), as well as having been indicated as a new molecular targeted site to treat neuroblastoma ( Yoshida et al, 2020 ). PLK1 ( Iliaki et al, 2021 ), EPHK10 , and KIF4A also play important roles as prognostic indicators or as targeted therapy sites for the progression of multiple tumors, such as pancreatic cancer ( Zhu et al, 2021 ), esophageal squamous cell carcinoma ( Li et al, 2021 ), bladder cancer ( Zheng et al, 2021 ), and lung cancer ( Kirienko et al, 2021 ). Furthermore, EPHA10 has already been approved as a potential therapeutic target of prostate cancer ( Nagano et al, 2014 ), and high EPHA10 expression correlated with lymph node metastasis of breast cancer ( Nagano et al, 2013 )—the type of malignant behavior that usually predicts a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%